PENGARUH MINAT DAN PELATIHAN TERHADAP PEMANFAATAN SISTEM INFORMASI MANAJEMEN YANG BERIMPLIKASI PADA KINERJA PEGAWAI - Rukhiyat Syahidin; Bugie Zurisdianto Pamungkas (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
Hospitals are service providers, by exercising their management capabilities, they are expected to be able to provide high quality services. Based on the health service performance achievements of the RSM Bandung Hospital in July-September 2024, the Bed Occupancy Rate (BOR) achievements are not yet in the ideal category, namely 53.99%, 47.41% and 50.76. Problems in implementing this performance are caused by a lack of training. This research aims to analyze the influence of interest and training on the use of management information systems and their impact on employee performance at RSM Bandung Hospital. This research methodology uses a quantitative research approach. The research subjects were employees at RSM Bandung Hospital with a sample of 68 people. The data analysis used is path analysis, correlation coefficient analysis and coefficient of determination analysis. The research results show that interest in utilizing management information systems (X1), training in management information systems (X2), utilization of management information systems (Y) and employee performance (Z), has a moderate to strong score with a value of 62.6% - 91.2% , the direct effect of interest in using management information systems on employee performance is 0.031 (3.1%) smaller than the direct effect of management information system training on employee performance of 0.378 (37.8%) or (X1-Z < X2-Z or 3.1% < 37.8%). The correlation value between the interest variable and training is 0.514 (medium), and the correlation value between utilization and employee performance is 0.227 (low). Therefore, it is recommended that the Director of RSM Bandung Hospital evaluate the guidelines for human resource management which it is hoped can be used as a reference that continues to be improved in order to achieve the goal of quality and integrity human resources